2022
DOI: 10.26633/rpsp.2022.55
|View full text |Cite
|
Sign up to set email alerts
|

Diretrizes de 2021 da Organização Mundial da Saúde sobre o tratamento medicamentoso da hipertensão arterial: repercussões para as políticas na Região das Américas

Abstract: A doença cardiovascular (DCV) é a principal causa de morte nas Américas, e a pressão arterial elevada é responsável por mais de 50% dos casos de DCV. Nas Américas, mais de um quarto das mulheres adultas e quatro de cada dez homens adultos têm hipertensão arterial, sendo que diagnóstico, tratamento e controle estão abaixo do ideal. Em 2021, a Organização Mundial da Saúde (OMS) divulgou uma atualização das diretrizes para o tratamento medicamentoso da hipertensão arterial em adultos. Esta publicação ressalta o p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…When connecting health systems design and performance to hypertension in migrant populations in the region, evidence indicated that actions must be following the individual’s needs, risks and exposures to provide a timely response for informed decision-making ( 64 ). To counteract hypertension in the region, initiatives such as the model Hearts in the Americas led by the Pan American Health Organization (PAHO), which supports and fosters cardiovascular disease prevention and its risk factors in collaboration with the Ministries of Health, have been developed ( 65 ). This technical package follows the World Health Organization (WHO) guidelines and comprises healthy lifestyle counseling, hypertension treatment and cardiovascular risk assessments while reducing specific care gaps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When connecting health systems design and performance to hypertension in migrant populations in the region, evidence indicated that actions must be following the individual’s needs, risks and exposures to provide a timely response for informed decision-making ( 64 ). To counteract hypertension in the region, initiatives such as the model Hearts in the Americas led by the Pan American Health Organization (PAHO), which supports and fosters cardiovascular disease prevention and its risk factors in collaboration with the Ministries of Health, have been developed ( 65 ). This technical package follows the World Health Organization (WHO) guidelines and comprises healthy lifestyle counseling, hypertension treatment and cardiovascular risk assessments while reducing specific care gaps.…”
Section: Resultsmentioning
confidence: 99%
“…The initiative is being implemented in 26 countries of the region, including Mexico, Costa Rica, Colombia, Peru, Chile, Argentina, and Brazil, and has improved hypertension control. However, underfunding and pilot implementation limitations remain in some countries, and specific consideration of migrant communities needs further development ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Com esses dados, analisar os riscos associados a farmacoterapia presente, avaliar cada medicamentos por sua elegibilidade a ser interrompido, como também priorizar as Revista Eletrônica Multidisciplinar de Investigação Científica ISSN: 2764-4987 DOI: https://doi.org/10.56166/remici.2023.5.v2n3.15.29 medicações a serem descontinuadas. Ademais, o farmacêutico promove a atenção farmacêutica com ações de autocuidado, educação em saúde, promoção do uso racional de fármacos, visando uma resposta positiva do paciente ao tratamento, também contribuindo no controle de agravos crônicos (GONÇALVES, 2021;NASCIMENTO, 2022;FERREIRA et al, 2022;MALTA et al, 2022;CAMPBELL et al, 2022) De acordo com a OMS, seis pilares são fundamentais para incorporação da atenção farmacêutica de modo que seu funcionamento ocorra plenamente, sendo os serviços ofertados, a força de trabalho, informação, acesso a medicamentos essenciais, vacinas e tecnologia, financiamento e liderança (GONÇALVES, 2021).…”
Section: Atenção Farmacêutica Para Promoção Do Uso Racional De Medica...unclassified
“…High blood pressure is the most significant reversible risk factor for the development of these diseases and deaths; more than half of CVD cases and 17% of deaths overall in the Americas can be attributed to high blood pressure. About 8% of health expenditures in the region are related to hypertension, which demonstrates a sensible use of resources, since controlling high blood pressure reduces both mortality rates and cases of disability, in addition to presenting a very positive and cost-effective cost-benefit ratio in most situations [8,10].…”
Section: Introductionmentioning
confidence: 99%